Mapping the spatial distribution of poverty using satellite imagery in Thailand. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
The leave no one behind principle of the 2030 Agenda for Sustainable Development requires appropriate indicators for different segments of a country population. This entails detailed, granular data on population groups that extend beyond national trends and averages. ADB collaborated with the National Statistical Office of Thailand and the Word Data Lab for the feasibility study, which aimed to enhance the granularity, cost-effectiveness, and compilation of high-quality poverty statistics in Thailand.
Keywords: Information technology -- Thailand; Electronic book